2011
DOI: 10.1016/j.niox.2011.10.001
|View full text |Cite
|
Sign up to set email alerts
|

The potent activity of sulfated polysaccharide, ascophyllan, isolated from Ascophyllum nodosum to induce nitric oxide and cytokine production from mouse macrophage RAW264.7 cells: Comparison between ascophyllan and fucoidan

Abstract: Ascophyllan isolated from the brown alga Ascophyllum nodosum is a fucose-containing sulfated polysaccharide, which has similar but distinct characteristic monosaccharide composition and entire chemical structure to fucoidan. In this study, we examined the effects of ascophyllan, fucoidan isolated from A. nodosum (A-fucoidan), and fucoidan from Sigma (S-fucoidan) as a representative fucoidan derived from other source (Fucus vesiculosus) on mouse macrophage cell line RAW264.7 cells. No significant cytotoxic effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 56 publications
1
61
0
1
Order By: Relevance
“…Besides some structural and bioactive similarities between fucoidan and ascophyllan (Heinzelmann et al 1998, Nakayasu et al 2009), our previous study demonstrated that ascophyllan showed a growth-promoting activity on MDCK cells, while fucoidan was rather toxic to this cell line (Jiang et al 2010). During the course of our comparative studies on the cellular level biological activities of sulfated polysaccharides from different seaweed species, we found that F. vesiculosus fucoidan, which is the only commercially available one, was highly cytotoxic to RAW264.7 cells, whereas ascophyllan and fucoidan isolated from A. nodosum showed no significant cytotoxicity on RAW264.7 cells up to 1,000 μg mL -1 (Jiang et al 2011). Fucoidans isolated from several algal species including commercially available fucoidan have been reported to possess numerous biological activities such as anticoagulant (Pereira et al 1999), antithrombotic activities (Kusaykin et al 2008), antiviral (Karmakar et al 2010, Sinha et al 2010, antitumor, anti-inflammatory (Cumashi et al 2007, Croci et al 2011), immuno-modulatory (Raghavendran et al 2011, and apoptosis-inducing activities (Jin et al 2010.…”
Section: Methodsmentioning
confidence: 88%
See 4 more Smart Citations
“…Besides some structural and bioactive similarities between fucoidan and ascophyllan (Heinzelmann et al 1998, Nakayasu et al 2009), our previous study demonstrated that ascophyllan showed a growth-promoting activity on MDCK cells, while fucoidan was rather toxic to this cell line (Jiang et al 2010). During the course of our comparative studies on the cellular level biological activities of sulfated polysaccharides from different seaweed species, we found that F. vesiculosus fucoidan, which is the only commercially available one, was highly cytotoxic to RAW264.7 cells, whereas ascophyllan and fucoidan isolated from A. nodosum showed no significant cytotoxicity on RAW264.7 cells up to 1,000 μg mL -1 (Jiang et al 2011). Fucoidans isolated from several algal species including commercially available fucoidan have been reported to possess numerous biological activities such as anticoagulant (Pereira et al 1999), antithrombotic activities (Kusaykin et al 2008), antiviral (Karmakar et al 2010, Sinha et al 2010, antitumor, anti-inflammatory (Cumashi et al 2007, Croci et al 2011), immuno-modulatory (Raghavendran et al 2011, and apoptosis-inducing activities (Jin et al 2010.…”
Section: Methodsmentioning
confidence: 88%
“…To estimate NO level in RAW264.7 cells, nitrite, a stable reaction product of NO with molecular oxygen, was measured by Griess assay as described previously (Jiang et al 2011). In brief, adherent RAW264.7 cells in 96-well plates (3 × 10 4 cells well -l ) were incubated with varying concentrations of test samples for 24 h in the growth medium at 37°C, and then the nitrite levels in the culture medium were measured. )…”
Section: Nitrite Assay For the Estimation Of Nitric Oxide (No)mentioning
confidence: 99%
See 3 more Smart Citations